The Effect of Thin Capitalization, Transfer Pricing, and Sales Growth on Tax Avoidance in Companies Listed on the Indonesia Stock Exchange - Ni Putu Nadia Devasari; Ni Putu Budiadnyani; I Nyoman Sunarta; I G.A. Desy Arlita (Universitas Muhammadiyah Makassar, 2025)
This study investigates the influence of thin capitalization, transfer pricing, and sales growth on tax avoidance in companies listed on the Indonesia Stock Exchange (IDX), specifically within the food and beverage manufacturing subsector from 2019 to 2023. The research aims to explore how internal financial strategies contribute to tax avoidance behaviors. A quantitative approach was employed using secondary data sourced from published financial statements. A total of 109 valid company-year observations were analyzed after removing 24 outliers from the initial dataset. The variables were tested using multiple linear regression analysis via SPSS, with a significance level set at 5%. The results indicate that thin capitalization has a positive and significant effect on tax avoidance, suggesting that companies leverage debt financing to reduce taxable income. Similarly, transfer pricing practices also show a significant positive relationship, implying the strategic allocation of intra-group transactions to lower tax obligations. Sales growth is found to positively and significantly affect tax avoidance, indicating that growing companies tend to adopt more aggressive tax strategies to maintain post-tax profitability. The adjusted R² value of 0.674 suggests that 67.4% of the variation in tax avoidance is explained by the model. These findings support agency theory, which posits that managers act in their own interest, often engaging in tax minimization to enhance financial performance and shareholder value. The study contributes to the understanding of corporate tax behavior in emerging markets and informs policymakers of the need for stricter regulations on intercompany transactions and capital structure management